2010
DOI: 10.1021/bi100486s
|View full text |Cite
|
Sign up to set email alerts
|

Phosphomimetic Substitution of CytochromecTyrosine 48 Decreases Respiration and Binding to Cardiolipin and Abolishes Ability to Trigger Downstream Caspase Activation

Abstract: Mammalian cytochrome c (Cytc) transfers electrons from the bc(1) complex to cytochrome c oxidase (CcO) as part of the mitochondrial electron transport chain, and it also participates in type II apoptosis. Our recent discovery of two tyrosine phosphorylation sites in Cytc, Tyr97 in bovine heart and Tyr48 in bovine liver, indicates that Cytc functions are regulated through cell signaling. To characterize the role of Cytc tyrosine phosphorylation in detail using an independent approach, we here overexpressed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 50 publications
7
105
0
1
Order By: Relevance
“…In both cases, changes in the kinetics of complex IV were observed when using the (at least partially) phosphorylated cytochrome c, which were reverted by alkaline phosphatase treatment. With the Tyr49 modified cytochrome c purified from liver, a twofold decrease in the maximal rate of isolated complex IV was observed (229), similar to what was observed when mutating this residue to Glu to mimic phosphorylation (159). This Glu49 cytochrome c also showed a lower redox potential by 45 mV, had a 30% lower binding affinity to cardiolipin, and was unable to catalyze cardiolipin oxidation or induce caspase-3 activity, which are events linked to the proapoptotic role of cytochrome c when released from the inner mitochondrial membrane (159).…”
Section: Cytochrome C and Complex Iv Phosphorylationsupporting
confidence: 67%
See 2 more Smart Citations
“…In both cases, changes in the kinetics of complex IV were observed when using the (at least partially) phosphorylated cytochrome c, which were reverted by alkaline phosphatase treatment. With the Tyr49 modified cytochrome c purified from liver, a twofold decrease in the maximal rate of isolated complex IV was observed (229), similar to what was observed when mutating this residue to Glu to mimic phosphorylation (159). This Glu49 cytochrome c also showed a lower redox potential by 45 mV, had a 30% lower binding affinity to cardiolipin, and was unable to catalyze cardiolipin oxidation or induce caspase-3 activity, which are events linked to the proapoptotic role of cytochrome c when released from the inner mitochondrial membrane (159).…”
Section: Cytochrome C and Complex Iv Phosphorylationsupporting
confidence: 67%
“…With the Tyr49 modified cytochrome c purified from liver, a twofold decrease in the maximal rate of isolated complex IV was observed (229), similar to what was observed when mutating this residue to Glu to mimic phosphorylation (159). This Glu49 cytochrome c also showed a lower redox potential by 45 mV, had a 30% lower binding affinity to cardiolipin, and was unable to catalyze cardiolipin oxidation or induce caspase-3 activity, which are events linked to the proapoptotic role of cytochrome c when released from the inner mitochondrial membrane (159). The Tyr98-phosphorylated cytochrome c from heart generated sigmoidal kinetics in isolated complex IV and exhibited a marked blue shift of the 695-nm spectral peak that reflects the interaction of the c heme with surrounding Met residues (119), also suggesting that a high fraction of cytochrome c molecules in the preparation contained this modification.…”
Section: Cytochrome C and Complex Iv Phosphorylationsupporting
confidence: 67%
See 1 more Smart Citation
“…It has recently been reported that tyrosine 48 gets phosphorylated under homeostatic conditions [37,38], with the concomitant effect on the availability of Cc to activate caspases [39,40]. Nitration and phosphorylation of Cc at the same tyrosine residue are mutually exclusive [41] but inhibit Cc-dependent caspases activation with a similar efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…impair both the electron donation to CcO and the activation of caspase-9 mediated by Apaf-1 in vitro (26,27). Notably, nitration of this residue also hinders the ability of Cc to activate Apaf-1 (28)(29)(30).…”
Section: Significancementioning
confidence: 99%